Analysis of Fatigue Life for Firing Pin of Chain Demolition Equipment based on Workbench - Jiaju Ren; Qinglei Wang; Wei Liu; Xiaoyou Wang; Lu Feng (Jixie chuandong)
The firing pin of chain demolition equipment are prone to fatigue damage under repeated loads， threaten the quality of chain products. In order to study the rule of firing pin fatigue damage， using the workbench software to perform the finite element analysis of the firing pin. Firstly， through the static strength analysis， the weak parts of the firing pin are determined， on this basis， the fatigue life is calculated， and the fatigue life of the firing pin is obtained. Comparing the data with the actual verification， the results show that the effect of the two methods is consistent and the validity of the finite element analysis is verified， it also provides some technical reference for the following equipment maintenance and structure optimization.